IMPLEMENTASI ALGORITMA CHUA CHAOTIC NOISE PADA ENKRIPSI CITRA RGB - Lubis, Utami Rahma Sari; Mesran, Mesran; Zebua, Taronisokhi (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2017)
Now this information technology users using computers as his media greatly increased .An effective security of a system was technology information is really needed to day-to-day activities , the issue of security and secrecy is one of the important aspect of a message , data , or information. One of them is image , image is one part of the department of multimedia of what is important. The image of presenting information visually and information presented by an image richer than served in a textual. One way to secure imagery is with the process of encryption , encryption is the process of turning plaintext into chipertext , one of the methods that could be used is an algorithm chua chaotic noise that is the algorithms that having a manner of working with each pixel count that were on the image of pictures and then do rotation pixels in vertical synchronization and horizontal based on the length of pixels of any result rotation pixel image so that encryption would come out the more random. Sensitivity his on the early can also cause to change a significant impact on his iteration. Sensitivity is very talk in cryptography that corresponded to the principle of diffusion. To the principle of this diffusion then transformation of one bit of an initial value of chaos can cause chipertext still not succeed in decryption